GAMBARAN PELAKSANAAN PIJAT OKSITOSIN OLEH BIDAN PRAKTIK MANDIRI DI KOTA PEKALONGAN - Sri Hidayati; Supriyo .; Ahmad Baequny (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2016)
Oxytocin massage is the massages on the neck area, backbone or throughout at backbone (vertebrae)until the fifthuntil the sixth costae bones. Massagging the neck and backbone can stimulate the production of oxytocin hormone. Failure in the process of breastfeeding is often caused by the onset of the problem, both the mother and the baby, either because milk production is less. To facilitate milk production can be done to stimulate the oxytocin reflex namely with oxytocin massage. The design of this research is a descriptive with cross sectional approach. The  population in this research is all the midwives who held practice independently in Pekalongan city. Samples in this research using all the total population that numbered 42 respondents. The results showed thatthe majority (54.8%) of respondents have implemented a massage oxytocin on postpartum mother and a small proportion (45.2%) do not carry out massage oxytocin. Respondents who have implemented massage oxytocin , they do so by massaging directly to postpartum mother once taught his / her family so hopefully they can do it independently at home . By doing oxytocin regular massage can stimulate the production of the hormone oxytocin and will be able to increase milkproduction. Suggested for health workers , especially midwives should be able to apply the massage oxytocin on postpartum mother that all milk production more smoothly because it has proven its benefits and nursing mothers are expected to carry out a massage oxytocin in accordance with what has been taught .